Klaus Koschorke i koncepcja historii światowego chrześcijaństwa w ujęciu szkoły monachijskiej - Hermann, Adrian; Burlacioiu, Ciprian (Annales Missiologici Posnanienses, 2016)
This article takes a look back at the last twenty years of what some have called the “Munich School of World Christianity” and presents the research of this group of scholars, who are working or have worked at Ludwig-Maximilians-Universität München, Germany. Its central focus highlights on the career and scholarly work of the groups Spiritus rector, Klaus Koschorke, who held the chair for Early and Global History of Christianity in the Faculty of Protestant Theology from 1993 to 2013. In this way, the reader, on the one hand, is introduced to the most important scholarly concepts, studies, and international conferences of the “Munich School” and, on the other hand, is given an overview of recent research projects dealing with indigenous Christian elites in Asia and Africa.